Digital, Adaptive, and Leadership: Keys to Sustainable Business - Daud, Ilzar; Karsim, Karsim (Universitas Bangka Belitung, 2025)
The rise of digital technologies has reshaped the business landscape, pushing organizations to adapt to remain competitive. This study explores how Digital Technology, Organisational Culture, and Leadership Skills relate to Organisational Sustainability, with a particular focus on the industrial sector in West Java. Data were collected from employees and leaders at various levels using a questionnaire, with 162 respondents. The analysis involved testing construct validity and reliability (through Cronbach's alpha and Composite Reliability), as well as conducting path analysis to evaluate direct and indirect effects among independent, mediating, and dependent variables. The results show that adopting digital technologies, an improved organisational culture, and strong leadership competencies all contribute to greater organisational resilience and sustainability. However, the study also highlights a gap: many organisations still lack an adaptive culture and the essential leadership skills to navigate ongoing technological change. These findings offer valuable insights for practitioners and organizational leaders is to develop an inclusive and innovative organizational culture alongside adaptable leadership systems, while also embracing digital transformation in a way that responsibly addresses its social and ethical implications such as privacy, data security, and environmental sustainability to ensure long-term resilience, relevance, and positive impact on all stakeholders.